Juan Francisco Domínguez Domínguez, Arias Montano y sus maestros, Madrid, Ediciones Clásicas, 2013, 214 pp. ISBN 978-84-7882-781-1 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Juan Francisco Domínguez Domínguez, Arias Montano y sus maestros, Madrid, Ediciones Clásicas, 2013, 214 pp. ISBN 978-84-7882-781-1